ARBUSCULAR MYCORRHIZAL FUNGI (AMF) CHARACTERIZATION IN RHIZOSPHERE of Gigantochloa atter - Fatimah Mansir; Hafsan Hafsan; Eka Sukmawaty; Masriany Masriany (Jurnal Biotek, 2021)
Mycorrhizae are typical structures found in a plant's root system found symbiotic mutualism between fungi (myces) and roots (rhiza). Mycorrhizae have an essential role for plants because they can increase water and nutrient uptake, especially phosphorus absorption. The purpose of this study was to determine the mycorrhizal genera on the roots of parring bamboo plants (Gigantochloa atter) in Sabantang Hamlet, Toddopulia Village, Tanralili District, Maros Regency because there is no scientific information regarding this issue. This research was conducted with the wet filter method or sieving. The isolation of spores from the rhizosphere of Gigantochloa atter samples was carried out by referring to the pouring method and wet sieving using a stratified filter set. Staining techniques were used to observe the colonization of arbuscular mycorrhizal structures in the roots of the sample plants. The results showed that 27 spores were found, consisting of 15 spores of the Glomus genera, three spores of the Gigaspora genera, and nine Acaulospora genera. Observation of the root structure has not shown the presence of vesicular and arbuscular. However, only hyphae and spore structures were found because the mycorrhizal hyphae in Gigantochloa atter have not yet reached the infection stage to form arbuscular or vesicular structures